Obesity Model in White Male Wistar Rats: The Impact of Moringa (Moringa Oleifera) Flower Extract on Pancreatic Function as Deduced from Serum Amylase and Lipase Levels and the Histopathological Image of the Pancreas - Devy; Jansen; Yani, Herlina (International Journal of Public Health Excellence (IJPHE), 2024)
Diabetes and obesity go hand in hand. Antidiabetic drugs are effective in treating diabetes. However, currently available antidiabetic drugs are too expensive, do not work, and cause major side effects. A significant therapeutic option for Diabetes Mellitus and obesity is using bioactive chemicals produced by plants. This compound is efficacious, easily accessible, safe, and affordable. The main aim of this study was to determine whether pancreatic extract from Moringa oleifera flowers affected blood amylase and lipase levels, as well as the histological appearance, of obese male Wistar white rats (Rattus norvegicus). This is a True experimental study, with the research design used as a test control Group Design. The research data was then analyzed with the help of SPSS using ANOVA and Post Hoc Test with LSD technique. This researcher used 24 male rats. Treatment with Moringa oleifera flower extract improves pancreatic function in obese Wistar white rats by reducing serum lipase and amylase levels. The results of research on serum lipase and amylase levels showed that a dose of 600mg/Kg BW improved pancreatic function in white rats of the Wistar strain that were obese.